The intricate interplay between cancer stem cells and cell-of-origin of cancer: implications for therapeutic strategies - Bamodu, Oluwaseun Adebayo; Chung, Chen-Chih; Pisanic, Thomas R.; Wu, Alexander T. H. (Frontiers in Oncology, 2024)
Background: Cancer stem cells (CSCs) have emerged as pivotal players in tumorigenesis, disease progression, and resistance to therapies. Objective: This comprehensive review delves into the intricate relationship between CSCs and the cell-of-origin in diverse cancer types. Design: Comprehensive review of thematically-relevant literature. Methods: We explore the underlying molecular mechanisms that drive the conversion of normal cells into CSCs and the impact of the cell-of-origin on CSC properties, tumor initiation, and therapeutic responses. Moreover, we discuss potential therapeutic interventions targeting CSCs based on their distinct cell-of-origin characteristics. Results: Accruing evidence suggest that the cell-of-origin, the cell type from which the tumor originates, plays a crucial role in determining the properties of CSCs and their contribution to tumor heterogeneity. Conclusion: By providing critical insights into the complex interplay between CSCs and their cellular origins, this article aims to enhance our understanding of cancer biology and pave the way for more effective and personalized cancer treatments.